GENDER ASPECTS IN THE FORMATION OF PROFESSIONAL ORIENTATION OF SUBJECTS OF SPORTS ACTIVITIES - Tetiana Bulhakova; Galіna Zhukova ("Scientific Information Agency "Science-technologies-information" LLC, 2021)
Gender stereotypes are intertwined in relations in society, reflect gender differences, and consolidate traditional gender roles. The concept of gender stereotype means the ability of a person to generally assess the relationships of people in the world and is the basis for inferences and uncritical conclusions. The positive function of stereotypes is the person will be able to react quickly to the changes even with limited data. The process of cognition is a reflection of objective reality, in which stereotypes often have a conservative effect. They form erroneous knowledge and ideas, which negatively affect the processes of interpersonal interaction.